What is the evidence for efficacy of advance care planning in improving patient outcomes? A systematic review of randomised controlled trials - Chetna Malhotra; Mahham Shafiq; Ada Portia Macarubbo Batcagan-Abueg (BMJ Open)
Objectives To conduct an up-to-date systematic review of all randomised controlled trials assessing efficacy of advance care planning (ACP) in improving patient outcomes, healthcare use/costs and documentation.Design Narrative synthesis conducted for randomised controlled trials. We searched electronic databases (MEDLINE/PubMed, Embase and Cochrane databases) for English-language randomised or cluster randomised controlled trials on 11 May 2020 and updated it on 12 May 2021 using the same search strategy. Two reviewers independently extracted data and assessed methodological quality. Disagreements were resolved by consensus or a third reviewer.Results We reviewed 132 eligible trials published between 1992 and May 2021; 64% were high-quality. We categorised study outcomes as patient (distal and proximal), healthcare use and process outcomes. There was mixed evidence that ACP interventions improved distal patient outcomes including end-of-life care consistent with preferences (25%; 3/12 with improvement), quality of life (0/14 studies), mental health (21%; 4/19) and home deaths (25%; 1/4), or that it reduced healthcare use/costs (18%; 4/22 studies). However, we found more consistent evidence that ACP interventions improve proximal patient outcomes including quality of patient–physician communication (68%; 13/19), preference for comfort care (70%; 16/23), decisional conflict (64%; 9/14) and patient-caregiver congruence in preference (82%; 18/22) and that it improved ACP documentation (a process outcome; 63%; 34/54).Conclusion This review provides the most comprehensive evidence to date regarding the efficacy of ACP on key patient outcomes and healthcare use/costs. Findings suggest a need to rethink the main purpose and outcomes of ACP.PROSPERO registration number CRD42020184080.